(untitled) (Czech Journal of International Relations, 2014)
The aim of this paper is to examine the consequences of a failure to make a preliminary reference from the point of view of consumer organizations striving for the protection of collective consumer rights. Also, this paper argues against a strict application of the principle of procedural autonomy of Member States, as it makes the enforcement of consumer rights practically impossible, in particular with respect to Directive 2009/22/EC of the European Parliament and of the Council of 23 April 2009 on injunctions for the protection of consumers’ interests (the Injunctions Directive). The author discusses both judicial and extrajudicial remedies that are available in case of a failure to make a preliminary reference to the Court of Justice of the European Union. She believes that procedural rules and the specific conditions for obtaining damages based on the Francovich judgment are not sufficiently harmonized throughout the European Union.